Anti-insulin antibodies in dogs with naturally occurring diabetes mellitus. - Davison, L; Ristic, J; Herrtage, M; Ramsey, I; Catchpole, B (2003)
The presence of anti-insulin antibodies was determined by ELISA in serum samples from 30 diabetic dogs receiving bovine insulin therapy and 30 normoglycaemic dogs. Twenty of the diabetic dogs had significant reactivity to both bovine (heterologous) and porcine (homologous) insulin compared to control dogs. In contrast there was no significant difference between the two populations in reactivity to canine distemper virus (CDV) or canine thyroglobulin. The high degree of correlation between anti-bovine insulin and anti-porcine insulin antibodies suggested cross-reactivity which was confirmed by performing a competition ELISA, with antibody binding to bovine insulin inhibited by pre-incubating serum with porcine insulin. The insulin B-chain, rather than the A-chain was the most reactive component of the insulin molecule although in some cases, diabetics with antibody reactivity to whole insulin protein showed minimal reactivity to the individual subunits. The data suggest that treatment of diabetic dogs with bovine insulin can lead to anti-insulin antibody production. These antibodies cross-react with homologous insulin and recognise conformational as well as linear epitopes.